The Effect of Collaborative Strategic Reading (CSR) on Students’ Reading Comprehension of Narrative Text - Miming Oktorianisarry; Yulitriana Yulitriana; Susan Ira Nova; Maida Norahmi (The Study Program of English Education of Palangka Raya University, 2023)
There are difficulties faced by students in learning reading of the narrative text, such as difficulties to find details, translating new words, finding main ideas, and making inferences. This research was conducted to see the effect of Collaborative Strategic Reading (CSR) on students reading comprehension of narrative text by applying ‘preview’ for brainstorming, ‘click and clunk’ for translating new words, ‘get the gist’ for finding details, and main ideas, and ‘wrap up’ for making inferences. It is a quasi-experimental research with experimental and control groups. The sample was the eleventh-grade students of SMA Negeri 3 Palangka Raya. XI MIPA 3 and XI MIPA 2 classes were the experimental and control groups, and each consists of 37 students. Reading comprehension tests were used to collect the data. Since the data were normally distributed, the hypotheses were tested by using the independent sample t-test. The hypothesis testing results show that the obtained sig (2-tailed) was 0.027 and smaller than the probability value of sig. 0.05 (Sig. 0.027 < Sig. 0.05). Therefore, Ha was accepted and Ho was rejected. In other words, CSR significantly affects students’ reading comprehension of narrative text.